Scanning inteferometer for characterization of piezoelectric thin films and MEMS devices - Wei, Samuel Maozhe. (2009)
Microelectromechanical systems (MEMS) and nanoelectromechanical systems have been given much attention in recent years. Characterizations of piezoelectric materials are needed to analyze the properties of such materials. However, the piezoelectric properties of thin films have not been sufficiently investigated due to the lack of a widely accepted standard of characterization and the lack of reliable method for piezoelectric characterization. Different characterization systems, such as scanning laser Doppler vibrometer, single beam laser interferometer, double beam inteferometric system and scanning laser interferometer, had been devised to measure the displacement of the small vibrations. In this project, a scanning laser interferometer will be built. The advantages of the scanning laser interferometer include having high resolution, of up to 10-2 Å, and also the ability to measure the true displacement of the vibrations of the film, by producing a line scan of the sample. Five samples, of PZT/NZFO composite thick films, are fabricated using sol-gel processing and spin coating technique during the process of the Final Year Project. These five samples are then characterized to investigate the effect of PZT mass fraction on microstructure, magnetic, ferroelectric and dielectric properties. One of the samples, PZT-2, shows potentials to be a candidate for multifunctional application, with saturated magnetization and remnant polarization reaching 4.3emu/cc and 13.9μC/cm2 respectively, and with a dielectric permittivity of 230. During the course of the project, the author had encountered several problems when aligning the optical path of the scanning laser interferometer. This report will also discuss solutions the author implemented to overcome these obstacles.